Dietary supplementation of Vitamin E and selenium on performance and oxidative stability of meat of broiler chickens in a hot climate - Ekunseitan Deji Abiodun; Yusuf Azeez Olanrewaju; Ekunseitan Oluwakemi Florence; Alao Samuel Oluwaseunla; Allinson Adesewa Zainab (Agricultura Tropica et Subtropica, 2021)
With the increase in consumers’ concern for safe food, it is highly imperative for livestock farmers to adopt feeding practices that enhance good health and high-quality products. A 49-day trial was conducted to ascertain effect of vitamin E and selenium (VE + Se) on performance, haematological indices and oxidative stability of chicken meat. A total of 150 Ross 7-day-old chicks were weighed and allotted to five treatments comprising dietary levels of 0 mg VE + 0 mg SE (Control), 100 mg VE + 0.05 mg Se, 200 mg VE + 0.1 mg Se, 300 mg VE + 0.15 mg Se and 400 mg VE + 0.2 mg Se per kg of feed in a completely randomised design. Feed and water were provided ad libitum. The data collected on performance, haematological indices and oxidative stability of meat were subjected to a one-way analysis of variance in a completely randomised design. Performance indices were significantly (p < 0.05) influenced by VE + Se supplementation. Mean daily live-weight gain (48.68 g /bird /day) was highest (p < 0.05) in the 400 mg VE + 0.2 mg group. The mean daily feed intake (g /bird / day) was highest in birds fed the diet containing 200 mg VE + 0.1 mg. The least or best feed conversion ratio (FCR) was observed in the group fed 400 mg VE + 0.2 mg SE. Glutathione peroxidase (GSH-Px) increased as the level of VE + Se increased with the highest activity in 400 mg VE + 0.2 mg Se group. The highest packed cell volume, haemoglobin and red blood cell values were observed in birds fed the diet containing 400 mg VE + 0.20 mg Se. In conclusion, to ensure good performance of the chickens and improved oxidative stability of chicken meat in hot climate, feeding broilers VE + SE at 400 mg VE + 0.2 mg Se is recommended.